EFFECT OF MOTIVATION ON LECTURER PERFORMANCE AT THE INSTITUTE OF SOCIAL AND POLITICAL SCIENCES (IISIP), YAPIS BIAK - Handayani, Sri (Program Pascasarjana Universitas Negeri Makassar, 2019)
This study aims to analyze the effect of motivation on lecturer performance at the Institute of Social and Political Sciences (IISIP), Yapis Biak. Data collection is done by distributing questionnaires and conducting interviews involving all permanent lecturers who are active in the Yapis Biak Institute of Social and Political Sciences. The population in this study were 43 people. The data collection method used is a questionnaire. The research approach used is a qualitative approach and the data testing techniques used in this study are multiple linear regression analysis to prove the research hypothesis. The results of the study based on statistical tests, the results of multiple linear regression showed that motivation influenced the performance of lecturers at the Yapis Biak Institute of Social and Political Sciences with a regression coefficient of 0.808.